Understanding incremental densification – Determinants of residential infill on vacant lots - Ehrhardt, Denise; Behnisch, Martin; Michaeli, Mark; Jehling, Mathias (Landscape and urban planning, 2025)
•Approach allows to link landowners’ and developers’ interests to infill processes.•Spatial and regulatory prerequisites determine multi-family housing infill.•Multi-family housing infill is further depending on market rationalities.•Low-density housing infill is driven by individual landowners’ interests.•Most vacant lots remain undeveloped, despite the existence of building rights. Urban densification faces challenges due to the declining availability of land in urban areas worldwide and the need to balance various demands regarding the use of the remaining land, which can provide high ecological and social value. At the same time, in many residential areas, small-scale vacant lots with existing building rights can be found. The decision as to whether or not densification on these lots takes place depends on individual landowners’ decisions and takes place largely without the purview of strategic planning. Although small-scale densification potentials and processes can add up to substantial amounts, they remain poorly studied. With this study, we aim to contribute to a better understanding of which determinants drive or limit small-scale incremental densification processes on vacant lots. We employ logistic regression analysis using detailed infill data from 2011 to 2021 for the three main processes found: Vacant lots staying vacant, infill with low-density housing, and infill with multi-family housing. Applied to a German study area, we obtain good model results for infill with multi-family housing (AUC: 0.82) which showed to be highly dependent on parcel characteristics, limited by planning regulations, and driven by market interests. In contrast, the model results for low-density housing infill were rather poor, indicating the importance of individual landowner interests as well as the minor impact of market rationalities, spatial preconditions, and planning regulations. However, the predominant process observed in the study area was that vacant lots remained undeveloped, highlighting the enduring presence of urban vacant land despite the existence of building rights. The study contributes to understanding the complex dynamics of decentralised densification processes and highlights the need for nuanced approaches to incremental densification, considering landowner interests and regulatory frameworks.